Conductive carbon with curled lamellar structure and application thereof
Conductive carbon with a curled lamellar structure addresses the limitations of existing materials by forming a hollow three-dimensional network with improved dispersibility and conductivity, enhancing battery performance.
Patent Information
- Application Number
- CN202310737788.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2024-12-20
AI Technical Summary
Existing conductive carbon materials fail to meet the high requirements for specific capacity, charge and discharge cycle life, and cost-effectiveness in secondary batteries due to limitations in conductivity, dispersibility, and manufacturing challenges, particularly with materials like acetylene black, SP carbon black, Ketjen black, CNTs, and graphene.
Development of conductive carbon with a curled lamellar structure that forms a multi-chain or multi-ring network, featuring a hollow three-dimensional structure with improved dispersibility and elasticity, enhancing conductivity and reducing resistance.
The curled lamellar structure enhances conductivity by allowing better ion contact and forming a larger conductive network, maintaining low resistance and high conductivity even under volume changes, thus improving battery performance.
Smart Images

Figure CN119160871A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon materials, and in particular to conductive carbon with a curled sheet structure and applications thereof. Background Art
[0002] Generally, carbon materials (except diamond) have a certain conductivity and are often used to improve the conductivity of electrical insulating materials (such as resins, etc.), or for negative electrode materials, positive electrode packaging materials, conductive agents, etc. of batteries and secondary batteries (rechargeable lithium batteries). In recent years, with the vigorous development of the new energy industry, the demand for electric energy storage has increased sharply, and higher requirements have been put forward for high specific capacity (capacity per unit volume) and high charge and discharge cycle life of secondary batteries (rechargeable lithium batteries), which has greatly stimulated the application demand of conductive carbon materials in secondary batteries. Although, it is well known that after gaseous hydrocarbons or liquid hydrocarbons are gasified, they are partially oxidized (partially burned) under aerobic conditions, or both are in the absence of oxygen and high temperature, they can be cracked to generate solid elemental carbon and hydrogen, as well as some hydrocarbon by-products. But it is not easy to obtain conductive carbon materials with excellent comprehensive performance. First of all, from the perspective of application needs, secondary batteries have high requirements for the specific performance of conductive carbon materials: 1. High structurality to form a conductive network; such as: "Carbon black and secondary battery using the carbon black as a conductive agent" provided by the patent with application number 201480070298: The carbon black is composed of carbon black aggregates 2 with a ratio of the number of primary particles 1 (PPA) to the particle size d (nm) of the above primary particles 1 (PPA / d) of 8 or more. SP carbon black and Ketjen black also have similar branched structures, while CNTs carbon nanotubes have a one-dimensional long wire structure and graphene has a hexagonal grid sheet structure, all of which are conducive to the formation of a conductive network. 2. Having very high DBP oil absorption value and BET specific surface area; for example, as described in the patent application number 201480070298, “Carbon black and secondary battery using the carbon black as a conductive agent”, the carbon black (DBP) absorption value is 180 mL / 100 g. After the unified unit and expression, that is, the carbon black DBP oil absorption value is 180 ml / g; and as described in the Japanese patent “Carbon black” of “Patent No. 2014-221889”, the carbon black is characterized by satisfying the following conditions (1) to (3): (1) BET specific surface area is 350 to 650 m 2 / g; (2) DBP oil absorption is 270-340cm 3 / 100g; (3) The BET specific surface area of the agglomerate diameter described in JIS K6217-6 is 350 to 650 m 2 / g, DBP oil absorption 270~340cm 3 / 100g; cm 3That is, ml. After unifying the units and expressions, the carbon black DBP oil absorption value is 270-340 ml / g, and the BET specific surface area is 350-650 m 2 / g. 3. Has good dispersibility.
[0003] Secondly, from the perspective of carbon material products and process technology, the conductive carbon materials currently available include: SP carbon black, Ketjen black (carbon black), acetylene black (carbon black), CNTs carbon nanotubes, graphene, etc., as shown in the table above. Although there seem to be many varieties, according to the current actual industrial production processes and technologies, only acetylene black can be mass-produced in China (Jiaozuo Hexing Chemical Industry Co., Ltd.). Although acetylene black is also called conductive carbon black, it can be seen from the data in the table above that its conductivity and BET specific surface area are quite different from those of good products. If acetylene black is applied to secondary batteries, the addition ratio must be increased, which will lead to a decrease in the proportion of other important active ingredients in the battery, resulting in a decrease in the battery unit volume capacity and a shortened charge and discharge cycle life. It can only be used for low-end secondary batteries; in addition, the raw material required to produce acetylene black is expensive acetylene, which makes the product quite low in cost performance. The SP carbon black with better conductivity is produced by the Belgian factory of IMERYS of France, and the Ketjen black with good conductivity is produced by Lion Specialty Chemicals Co., Ltd. of Japan. These two products are not only expensive, but also have to be supplied to the global battery and non-battery markets, and their production capacity is very limited, making it difficult to meet the development needs of the secondary battery industry in the long term; as for carbon nanotubes and graphene, although they have better conductivity, they are difficult to manufacture, difficult to mass produce, and the manufacturing cost is too high. In addition, in practical applications, the problem of poor dispersion affecting the actual conductivity effect needs to be solved, and they can only be used in very small quantities like "MSG". In addition to the above products and corresponding process technologies, other conventional carbon material production technologies are difficult to create new conductive carbon materials that are easy to mass produce and expand.
[0004] In addition, materials such as CNTs and graphene require the addition of iron and nickel catalysts to control the crystal morphology and efficiency of carbon. The resulting CNTs, graphene and catalysts are mixed together and cannot be separated by simple screening methods. These metal components are harmful in secondary battery applications, and usually require the use of high-temperature metal evaporation, acid washing and other methods. High-temperature evaporation has problems such as long time, high energy consumption and low efficiency. Acid washing can easily cause environmental pollution and affect product quality. Summary of the invention
[0005] The present invention aims to solve the shortcoming in the prior art that common carbon materials cannot meet the requirements for battery use, and provides conductive carbon with a curled lamellar structure and applications thereof. The conductive carbon with a curled lamellar structure has a multi-chain or multi-ring network structure, has better dispersibility, and can form a conductive network in a larger range. The hollow space in the conductive carbon with a curled lamellar structure can further reduce resistance and increase conductivity; at the same time, it also has good elasticity and can more stably maintain low resistance and high conductivity.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] Conductive carbon with a curled lamellar structure, the conductive carbon with a curled lamellar structure comprising a conductive carbon monomer with a curled lamellar structure and / or a conductive carbon stack with a curled lamellar structure; the microstructure of the conductive carbon with a curled lamellar structure is a chain or ring formed by carbon atoms, and when further condensed and assembled into multiple chains or multiple rings to form a lamellar structure, dislocation and multiple curling occur to form a hollow three-dimensional structure; the conductive carbon monomer with a curled lamellar structure is a lamellar folded in one direction to form a U or V shape, or the conductive carbon monomer with a curled lamellar structure is a lamellar folded in the opposite direction and irregularly multiple times to form an N, M or W shape , or the conductive carbon monomer with a lamella curling structure is a lamella curled on a larger scale to form a C or G type curl; or the conductive carbon monomer with a lamella curling structure is a combination of at least two of U or V type folding, N or M or W type folding, C or G type curling that are repeated multiple times and folded in different directions; the conductive carbon stack with a lamella curling structure is a stack of at least two conductive carbon monomers with a lamella curling structure that exist at the same time; the hollow three-dimensional structure is a space that is not completely closed in a single curled lamella after the lamella is folded and curled into a three-dimensional shape, and that cannot enter each other when multiple curled lamellae are stacked.
[0008] Preferably, the conductive carbon stack with a sheet curling structure is a combined curling in which at least two of the following foldings exist simultaneously: U or V type folding, N or M or W type folding, and C or G type folding.
[0009] Preferably, in the conductive carbon with the curled sheet structure, the curled monomer length L is 20 to 2000 nm, the curled monomer width W is 20 to 2000 nm, the curled monomer height H is 20 to 2000 nm, and the sheet thickness δ is 10 to 20 nm.
[0010] Preferably, the DBP oil absorption value of the conductive carbon with a curled sheet structure is 300 to 800 ml / 100 g, and the BET specific surface area of the conductive carbon with a curled sheet structure is 200 to 800 m 2 / g.
[0011] Preferably, the iodine absorption value of the conductive carbon with the curled sheet structure is 200-1200 mg / g, and the electrical conductivity of the conductive carbon with the curled sheet structure is 1-2000 S / m.
[0012] Application of conductive carbon with curled lamellar structure, mixing conductive carbon with curled lamellar structure with other carbon materials or non-carbon materials to obtain conductive carbon material rich in curled lamellar structure, said conductive carbon material rich in curled lamellar structure is used for secondary battery negative electrode material or secondary battery positive electrode wrapping material or conductive agent or pigment carbon material.
[0013] Preferably, the conductive carbon material rich in curled lamellar structure includes conductive carbon of curled lamellar structure, carbon of other structures and non-carbon impurities, the conductive carbon content of the curled lamellar structure is ≥95%, the carbon content of other structures is ≤4%, and the non-carbon impurity content is ≤1%.
[0014] Preferably, the carbon with other structures includes amorphous carbon, carbon black and other forms of carbon.
[0015] Preferably, the non-carbon impurities include ash and volatile matter.
[0016] The beneficial effects of this technical solution are as follows:
[0017] 1. The conductive carbon with a curled sheet structure provided by the present invention has a microstructure of a chain or ring formed by carbon atoms, and when further condensed and assembled into a multi-chain or multi-ring sheet structure, dislocation and multiple curling occur to form a hollow three-dimensional structure: on the one hand, compared with SP carbon black, Ketjen black, acetylene black, CNTs carbon nanotubes, etc., it has a more complex multi-chain or multi-ring structure, with more open boundaries and incomplete ring structures, which can better contact and conduct with the ions of the material to be conductive, and can also form secondary connections between the conductive carbon materials to form a larger conductive network, resulting in better conductive performance; on the other hand, compared with graphene, it has a smaller particle size, and the curled three-dimensional structure is not prone to the actual specific surface area reduction caused by the overlap of the two-dimensional sheets of graphene. It has better dispersibility and a stable and effective specific surface area, and the actual surface of the sheet is larger than that of ordinary carbon black particles, which can form an effective point-to-surface contact with the ions of the material to be conductive, which can further reduce resistance and improve conductivity.
[0018] 2. The conductive carbon with a curled sheet structure provided by the present invention has hollow spaces that allow ions of conductive materials to enter and exit smoothly, and both the inside and outside can effectively contact with the conductive material ions, further reducing resistance and improving conductivity; at the same time, it also has good elasticity and can form flexible contact with the conductive material ions. When the conductive material changes in volume due to conduction, charging and discharging, thermal expansion and contraction, external force or other influences, no contact gap will appear, and low resistivity and high conductivity can be maintained more stably. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is an electron microscope photo of conductive carbon with a curled lamellar structure;
[0020] Figure 2 Schematic diagram of the size of the conductive carbon with curled sheet structure;
[0021] Figure 3 This is a 10,000-fold electron microscope photo of the conductive carbon with a curled lamellar structure (1μm scale);
[0022] Figure 4 This is a 20,000-fold electron microscope photo of the conductive carbon with a curled lamellar structure (500nm scale);
[0023] Figure 5 This is a 50,000-fold electron microscope photo of the conductive carbon with a curled lamellar structure (200nm scale);
[0024] Figure 6 This is an 80,000-fold electron microscope photo of the conductive carbon with a curled lamellar structure (100 nm scale);
[0025] Figure 7 The electron microscope photographs of the conductive carbon with curled lamellar structure and the carbon black with branched structure in the invention are compared;
[0026] Figure 8 A schematic diagram of the structure of the preparation device in the invention;
[0027] Fig. 9 It is a schematic diagram of the structure of the door twist block in the invention preparation device;
[0028] Among them: 1. microwave generator; 2. air-isolating waveguide; 201. first waveguide; 202. second waveguide; 203. wave-transmitting air-isolating plate; 3. waveguide / coaxial converter; 4. high breakdown strength coaxial transmission section; 5. low breakdown strength coaxial transmission section; 6. coaxial inner conductor; 7. raw material air inlet; 8. control air inlet; 9. outlet ionization zone; 10. door twist block; 11. anti-flow air pipe; 12. anti-flow hole; 13. λ / 4 anti-flow groove; 14. dynamic sealing structure; 15. air permeability; 16. circulating air collecting hood; 17. circulating air outlet; 1 8. Circulating air inlet; 19. Circulating air pipe; 20. Cooling purifier; 21. Circulating air pump; 22. Circulating air regulating valve; 23. Cooling collection bin; 301. Conductive carbon monomer with lamellar curling structure; 302. Conductive carbon stack with lamellar curling structure; 303. Branched carbon black; 401. U or V-shaped folding; 402. N or M or W-shaped folding; 403. C or G-shaped curling; 404. Combined curling; 501. Curled monomer length L; 502. Curled monomer width W; 503. Curled monomer height H; 504. Lamellar thickness δ. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0030] DBP oil absorption value: the volume of dibutyl phthalate absorbed by 100g of carbon black under specified test conditions (cm 3 ). It is used to characterize the aggregation degree of carbon black. The DBP value can calculate the void volume between carbon black aggregates, so it is a measure of the aggregation and agglomeration degree of carbon black. Therefore, generally, the higher the DBP oil absorption value, the stronger the structure and the better the conductivity.
[0031] EIS stands for electrochemical impedance spectroscopy. This data is positively correlated with resistivity, that is, the larger the EIS, the greater the resistivity and the worse the conductivity; it is negatively correlated with conductivity, that is, the smaller the EIS, the higher the conductivity and the better the conductivity.
[0032] BET specific surface area is the abbreviation of BET specific surface area test method, which is named because it is based on the famous BET theory.
[0033] like Figure 8 and Fig. 9 As shown: a device for preparing conductive carbon with a curled sheet structure, comprising a microwave generator 1, an air-isolating waveguide 2, a waveguide / coaxial converter 3, a high breakdown strength coaxial transmission section 4 and a low breakdown strength coaxial transmission section 5 connected in sequence, wherein the waveguide / coaxial converter 3, the high breakdown strength coaxial transmission section 4 and the low breakdown strength coaxial transmission section 5 are penetrated by a coaxial inner conductor 6, the waveguide / coaxial converter 3 is provided with a raw material air inlet 7, the high breakdown strength coaxial transmission section 4 or the low breakdown strength coaxial transmission section 5 is provided with a control air inlet 8, and the low breakdown strength coaxial transmission section 5 is provided with an outlet ionization zone 9.
[0034] The air-isolating waveguide 2 includes a first waveguide 201 and a second waveguide 202 , and a wave-transmitting air-isolating plate 203 is disposed between the first waveguide 201 and the second waveguide 202 .
[0035] Among them, the lower end of the waveguide / coaxial converter 3 is connected to the anti-flow air pipe 11 through a door twist block 10, and an anti-flow hole 12 is arranged on the door twist block 10, and a λ / 4 anti-flow groove 13 is arranged at the upper end of the anti-flow hole 12; the lower end of the coaxial inner conductor 6 passes through the anti-flow air pipe 11, and a dynamic sealing structure 14 is arranged at the lower end of the anti-flow air pipe 11.
[0036] The waveguide / coaxial converter 3 has an opening at the upper end and is connected to the lower end of the high breakdown strength coaxial transmission section 4 , and the upper end of the high breakdown strength coaxial transmission section 4 is connected to the lower end of the low breakdown strength coaxial transmission section 5 .
[0037] Among them, the high breakdown strength coaxial transmission section 4 is provided with a plurality of air holes 15, a circulating air collecting hood 16 is provided on the outside of the air hole 15, a circulating air outlet 17 is provided on the circulating air collecting hood 16, a raw material air inlet 7 and a circulating air inlet 18 are provided on the anti-circulation air pipe 11, the circulating air inlet 18 is connected to the circulating air outlet 17 through a circulating air pipe 19, and a cooling purifier 20, a circulating air pump 21 and a circulating air regulating valve 22 are provided on the circulating air pipe 19.
[0038] Wherein, a cooling collection chamber 23 is provided at the upper end of the outlet ionization zone 9 as shown.
[0039] The method for preparing conductive carbon with a curled sheet structure comprises the following steps:
[0040] Step 1: Inert gas is introduced through the raw material gas inlet 7 and the control gas inlet 8, and the inert gas fills the second waveguide 202, the waveguide / coaxial converter 3, the high breakdown strength coaxial transmission section 4, the low breakdown strength coaxial transmission section 5, the outlet ionization zone 9 and the internal space of the cooling collection chamber 23, and discharges the oxygen therein;
[0041] Step 2: After the oxygen content at the outlet ionization zone 9 is less than 0.5%, the microwave generator 1 is started, and the microwave passes through the gas isolation waveguide 2, the waveguide / coaxial converter 3, the high breakdown strength coaxial transmission section 4 and the low breakdown strength coaxial transmission section 5 in sequence, and the coaxial inner conductor 6 is adjusted to adjust the microwave electric field intensity at the outlet ionization zone 9;
[0042] Step 3, stop introducing inert gas, and introduce raw gas from the raw gas inlet 7, the raw gas fills the second waveguide 202 and the internal space of the waveguide / coaxial converter 3, and flows into the low breakdown strength coaxial transmission section 5 through the high breakdown strength coaxial transmission section 4, and at the same time, start the circulating gas pump 21 to make part of the raw gas circulate through the cooling purifier 20 and the circulating gas pipe 19 and return to the circulating gas inlet 18, adjust the circulating gas flow rate, so that the circulating flow rate of the raw gas is greater than the flow rate flowing into the low breakdown strength coaxial transmission section 5, and at the same time introduce control gas, the mixed gas of the raw gas and the control gas will fill the low breakdown strength coaxial transmission section 5, and adjust the flow rate of the control gas;
[0043] Step 4: When the mixed gas passes through the outlet ionization zone 9, it will be continuously ionized and generate high temperature, and chemical reaction will occur to produce conductive carbon with curled sheet structure and by-product tail gas;
[0044] Step 5, tail gas post-treatment: the by-product tail gas and the control gas that does not participate in the reaction form a mixed tail gas, and the conductive carbon carrying the curled sheet structure quickly leaves the outlet ionization zone 9 and enters the cooling collection chamber 23 for gas-solid separation.
[0045] Among them, the inert gas is argon, the raw gas is natural gas / methane, the intake volume of the raw gas is 8L / min, the microwave power is 12KW, the concentration of the raw gas is 11.8%, the circulating gas includes hydrogen, argon, nitrogen and CO / CO2, and the flow rates of hydrogen, argon, nitrogen, CO / CO2 are 10L / min, 10L / min, 10L / min and 30L / min respectively; the flow rate of the control gas is 120L / min.
[0046] The main reaction in this device is: CH4→C+2H2.
[0047] Example 1
[0048] like Figure 1-Figure 6 As shown, the conductive carbon with a curled lamellar structure includes a conductive carbon monomer 301 with a curled lamellar structure; the microstructure of the conductive carbon with the curled lamellar structure is a chain or ring formed by carbon atoms, and when further condensed and assembled into multiple chains or multiple rings to form a lamellar structure, dislocation and multiple curling occur to form a hollow three-dimensional structure; the conductive carbon monomer 301 with a curled lamellar structure is a lamellar folded in one direction to present a U or V-shaped fold 401, and the curled monomer length L501 in the conductive carbon with the curled lamellar structure is 20nm, the curled monomer width W502 is 20nm, the curled monomer height H503 is 20nm, and the lamellar thickness δ504 is 10nm.
[0049] The DBP oil absorption value of the conductive carbon with curled lamellar structure is 300ml / 100g, and the BET specific surface area of the conductive carbon with curled lamellar structure is 200m 2 / g; the iodine absorption value of the conductive carbon with a curled lamellar structure is 200 mg / g, and the electrical conductivity of the conductive carbon with a curled lamellar structure is 1 S / m.
[0050] Example 2
[0051] The conductive carbon with a curled lamellar structure includes a conductive carbon monomer 301 with a curled lamellar structure; the microstructure of the conductive carbon with a curled lamellar structure is a chain or ring formed by carbon atoms, and when further condensed and assembled into multiple chains or multiple rings to form a lamellar structure, dislocation and multiple curling occur to form a hollow three-dimensional structure; the conductive carbon monomer 301 with a curled lamellar structure is a lamellar folded in one direction to form a C or G type curl 403; the curled monomer length L501 in the conductive carbon with a curled lamellar structure is 2000nm, the curled monomer width W502 is 2000nm, the curled monomer height H503 is 2000nm, and the lamellar thickness δ504 is 20nm.
[0052] The DBP oil absorption value of the conductive carbon with curled lamellar structure is 427ml / 100g, and the BET specific surface area of the conductive carbon with curled lamellar structure is 437m 2 / g; the iodine absorption value of the conductive carbon with a curled lamellar structure is 346 mg / g, and the electrical conductivity of the conductive carbon with a curled lamellar structure is 640 S / m.
[0053] Example 3
[0054] The conductive carbon with a curled lamellar structure includes a conductive carbon monomer 301 with a curled lamellar structure and a conductive carbon stack 302 with a curled lamellar structure; the microstructure of the conductive carbon with a curled lamellar structure is a chain or ring formed by carbon atoms, and when further condensed and assembled into multiple chains or multiple rings to form a lamellar structure, dislocation and multiple curling occur to form a hollow three-dimensional structure; the conductive carbon monomer 301 with a curled lamellar structure is a lamellar folded in one direction to present a C or G type curl 403, and the conductive carbon stack 302 with a curled lamellar structure includes a U or V type fold 401 and a C or G type curl 403, and the curled monomer length L501 in the conductive carbon with a curled lamellar structure is 20 to 1000 nm, the curled monomer width W502 is 20 to 500 nm, the curled monomer height H503 is 20 to 500 m, and the lamellar thickness δ504 is 11 to 13 nm.
[0055] The DBP oil absorption value of the conductive carbon with curled lamellar structure is 564ml / 100g, and the BET specific surface area of the conductive carbon with curled lamellar structure is 227m 2 / g; the iodine absorption value of the conductive carbon with a curled lamellar structure is 475 mg / g, and the electrical conductivity of the conductive carbon with a curled lamellar structure is 840 S / m.
[0056] Example 4
[0057] The conductive carbon with curled sheet structure includes a conductive carbon monomer with curled sheet structure 301 and a conductive carbon stack with curled sheet structure 302; the microstructure of the conductive carbon with curled sheet structure is a chain or ring formed by carbon atoms, and when further condensed and assembled into multiple chains or multiple rings to form a sheet structure, dislocation and multiple curling occur to form a hollow three-dimensional structure; the conductive carbon monomer with curled sheet structure 301 is N or M or W-shaped folding 402 and C or G-shaped curling 403 at the same time. The combined curling 404 exists at the time, and the conductive carbon stack 302 with a lamellar curling structure includes N or M or W type folding 402, C or G type curling 403 and a combined curling 404. The curling monomer length L501 in the conductive carbon with the curled lamellar structure is 400-1600nm, the curling monomer width W502 is 300-1200nm, the curling monomer height H503 is 300-1200m, and the lamellar thickness δ504 is 13-15nm.
[0058] The DBP oil absorption value of the conductive carbon with curled lamellar structure is 610ml / 100g, and the BET specific surface area of the conductive carbon with curled lamellar structure is 244m 2 / g; the iodine absorption value of the conductive carbon with a curled lamellar structure is 490 mg / g, and the electrical conductivity of the conductive carbon with a curled lamellar structure is 1000 S / m.
[0059] Example 5
[0060] The conductive carbon with a curled lamellar structure includes a conductive carbon monomer 301 with a curled lamellar structure and a conductive carbon stack 302 with a curled lamellar structure; the microstructure of the conductive carbon with a curled lamellar structure is a chain or ring formed by carbon atoms, and when further condensed and assembled into multiple chains or multiple rings to form a lamellar structure, dislocation and multiple curling occur to form a hollow three-dimensional structure; the conductive carbon monomer 301 with a curled lamellar structure is a lamellar folded in one direction to present a U or V-shaped fold 401, and the conductive carbon stack 302 with a curled lamellar structure includes a U or V-shaped fold 401, an N or M or W-shaped fold 402 and a C or G-shaped curl 403. The curled monomer length L501 in the conductive carbon with a curled lamellar structure is 500-1800nm, the curled monomer width W502 is 500-1600nm, the curled monomer height H503 is 500-1600m, and the lamellar thickness δ504 is 12-16nm.
[0061] The DBP oil absorption value of the conductive carbon with curled lamellar structure is 674ml / 100g, and the BET specific surface area of the conductive carbon with curled lamellar structure is 394m 2 / g; the iodine absorption value of the conductive carbon with a curled lamellar structure is 841 mg / g, and the electrical conductivity of the conductive carbon with a curled lamellar structure is 1246 S / m.
[0062] Example 6
[0063] The conductive carbon with a curled lamellar structure includes a conductive carbon stack 302 with a curled lamellar structure; the microstructure of the conductive carbon with the curled lamellar structure is a chain or ring formed by carbon atoms, and when further condensed and assembled into multiple chains or multiple rings to form a lamellar structure, dislocation and multiple curling occur to form a hollow three-dimensional structure; the conductive carbon stack 302 with a curled lamellar structure includes a U or V-shaped fold 401, an N or M or W-shaped fold 402 and a C or G-shaped curl 403, and the curled monomer length L501 of the conductive carbon with the curled lamellar structure is 800 to 2000nm, the curled monomer width W502 is 800 to 2000nm, the curled monomer height H503 is 800 to 2000m, and the lamellar thickness δ504 is 14 to 19nm.
[0064] The DBP oil absorption value of the conductive carbon with a curled lamellar structure is 762 ml / 100 g, and the BET specific surface area of the conductive carbon with a curled lamellar structure is 613 m2 / g; the iodine absorption value of the conductive carbon with a curled lamellar structure is 1148 mg / g, and the electrical conductivity of the conductive carbon with a curled lamellar structure is 1632 S / m.
[0065] Example 7
[0066] The conductive carbon with curled sheet structure includes a conductive carbon monomer with curled sheet structure 301 and a conductive carbon stack with curled sheet structure 302; the microstructure of the conductive carbon with curled sheet structure is a chain or ring formed by carbon atoms, and when further condensed and assembled into multiple chains or multiple rings to form a sheet structure, dislocation and multiple curling occur to form a hollow three-dimensional structure; the conductive carbon monomer with curled sheet structure 301 is a U or V-shaped folding 401, an N or M or W-shaped folding 402 and a C or G-shaped curling 403. The combined curling 404 exists when the conductive carbon stack 302 with a lamellar curling structure includes a U or V type folding 401, an N or M or W type folding 402, a C or G type curling 403 and a combined curling 404. The curling monomer length L501 in the conductive carbon with the curled lamellar structure is 100 to 2000 nm, the curling monomer width W502 is 20 to 1500 nm, the curling monomer height H503 is 20 to 1500 m, and the lamellar thickness δ504 is 10 to 20 nm.
[0067] The DBP oil absorption value of the conductive carbon with curled lamellar structure is 800ml / 100g, and the BET specific surface area of the conductive carbon with curled lamellar structure is 800m 2 / g; the iodine absorption value of the conductive carbon with a curled lamellar structure is 1200 mg / g, and the electrical conductivity of the conductive carbon with a curled lamellar structure is 2000 S / m.
[0068] Embodiment 1-embodiment 7, it can be seen that: pure sheet curled structure conductive carbon monomer 301 and size is small, due to the small size resulting in low complexity of curled structure, such carbon particles are closer to amorphous carbon, so DBP oil absorption value, BET specific surface area, iodine absorption value, conductivity are very low. Similarly, pure sheet curled structure conductive carbon monomer 301 and size is large, large size can enhance the complexity of curled structure, but due to the single size resulting in hollow and gap can not be effectively filled, so DBP oil absorption value, BET specific surface area, iodine absorption value are improved, but conductivity is still low. In actual production, it is easier to obtain a stack of conductive carbon materials of curled sheet structure mixed with conductive carbon monomers of various sizes and structures, and conductive carbon materials of curled sheet structure of different sizes and structures are mixed, fill the gap, complement each other, and form a complex secondary network, which can greatly improve DBP oil absorption value, BET specific surface area, iodine absorption value, conductivity, especially the wider the size distribution range, the better the effect.
[0069] Example 8
[0070] The conductive carbon with curled sheet structure used in this embodiment is the conductive carbon material rich in curled sheet structure prepared in Example 1, including conductive carbon with curled sheet structure, carbon with other structures and non-carbon impurities, wherein the conductive carbon with curled sheet structure has a content of 95%, the carbon with other structures has a content of 4%, and the non-carbon impurities have a content of 1%; the carbon with other structures is amorphous carbon; the non-carbon impurities include ash and volatile matter. The conductive carbon material rich in curled sheet structure is used for negative electrode materials of secondary batteries.
[0071] When added at a ratio of 10 to 50%, the electrochemical impedance spectroscopy (EIS) can be reduced to 20 to 50, achieving excellent conductive properties.
[0072] Example 9
[0073] like Figure 7 As shown, the conductive carbon with curled sheet structure used in this embodiment is prepared in Example 2, and is rich in conductive carbon material with curled sheet structure, including conductive carbon with curled sheet structure, carbon with other structures and non-carbon impurities, wherein the conductive carbon content of the curled sheet structure is 96%, the carbon content of the other structures is 3.5%, the non-carbon impurity content is 0.5%, and the carbon with other structures is branched structure carbon black 303; the non-carbon impurities include ash and volatile matter. The conductive carbon material rich in curled sheet structure is used for secondary battery positive electrode wrapping material.
[0074] When added at a ratio of 10 to 50%, the electrochemical impedance spectroscopy (EIS) can be reduced to 20 to 50, achieving excellent conductive properties.
[0075] Example 10
[0076] The conductive carbon with curled lamellar structure used in this embodiment is the conductive carbon material rich in curled lamellar structure prepared in Example 3, including conductive carbon with curled lamellar structure, carbon with other structures and non-carbon impurities, wherein the conductive carbon with curled lamellar structure has a content of 97%, the carbon with other structures has a content of 2.5%, and the non-carbon impurities have a content of 0.5%; the carbon with other structures is carbon in other forms; and the non-carbon impurities include ash and volatile matter. The conductive carbon material rich in curled lamellar structure is used as a conductive agent.
[0077] When added at a ratio of 10 to 50%, the electrochemical impedance spectroscopy (EIS) can be reduced to 20 to 50, achieving excellent conductive properties.
[0078] Embodiment 11
[0079] The conductive carbon with curled lamellar structure used in this embodiment is the conductive carbon material rich in curled lamellar structure prepared in Example 4, including conductive carbon with curled lamellar structure, carbon with other structures and non-carbon impurities, and the conductive carbon content of the curled lamellar structure is 100%. The conductive carbon material rich in curled lamellar structure is used for pigment carbon material.
[0080] Usually, the coloring effect of carbon black can be described by the blackness and tinting strength of carbon black. The blackness is characterized by the reflectivity of the sample after the carbon black is added. Depending on the manufacturer and brand of the carbon black, the blackness value ranges from 40% to 25%. The lower the better. The tinting strength, depending on the manufacturer and brand of the carbon black, the value ranges from 94% to 145 ASTM%. The higher the better. The conductive carbon material in the present application forms a hollow three-dimensional structure due to the existence of dislocation and multiple curling; the conductive carbon monomer with a lamella curling structure is a lamella folded in one direction to form a U or V shape, or the conductive carbon monomer with a lamella curling structure is a lamella folded in the opposite and irregular direction to form an N or M or W shape, or the conductive carbon monomer with a lamella curling structure is a lamella curled on a larger scale to form a C or G shape; or the conductive carbon monomer with a lamella curling structure is a combination of at least two of U or V shape folding, N or M or W shape folding, C or G shape folding, and folding in different directions; the conductive carbon stack with a lamella curling structure is a stack of at least two conductive carbon monomers with a lamella curling structure coexisting; the hollow three-dimensional structure is a space that is not completely closed in a single curled lamella after the lamella is folded and curled into a three-dimensional shape, and that cannot enter each other when multiple curled lamellae are stacked. This structure enables the conductive carbon material in the present application to have excellent light absorption, with a blackness value of <25% and a tinting strength of >145 ASTM%.
[0081] Comparative Example
[0082] The performance comparison of conventional carbon materials, such as SP carbon black, Ketjen black EC300J, Ketjen black EC600JD, acetylene black (Hexing), CNTs carbon nanotubes and graphene with the conductive carbon material rich in curled sheet structure in this application is shown in the following table.
[0083]
[0084] From the above, it can be seen that the conductive carbon material rich in curled lamellar structure obtained in the present application has a very high structure to form a conductive network, a very high DBP oil absorption value and BET specific surface area and good dispersibility.
[0085] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification or equivalent change made to the above embodiment based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. Conductive carbon with a curled sheet structure, characterized in that: The conductive carbon with curled sheet structure includes conductive carbon monomer with curled sheet structure and / or conductive carbon stack with curled sheet structure; the microstructure of the conductive carbon with curled sheet structure is a chain or ring formed by carbon atoms, and when further condensed and assembled into multiple chains or multiple rings to form a sheet structure, it is dislocated and curled multiple times to form a hollow three-dimensional structure; the conductive carbon monomer with curled sheet structure is that the sheet is folded in one direction to form a U or V shape, or the conductive carbon monomer with curled sheet structure is that the sheet is folded in the opposite direction and irregularly multiple times to form an N, M or W shape, or the sheet is curled The conductive carbon monomer with a curved structure is a C or G-shaped curling of the lamellae on a larger scale; or the conductive carbon monomer with a curled lamellae structure is a combination of at least two of U or V-shaped folding, N or M or W-shaped folding, C or G-shaped curling, which are repeated multiple times and folded in different directions; the conductive carbon stack with a curled lamellae structure is a stack of at least two conductive carbon monomers with a curled lamellae structure that exist at the same time; the hollow three-dimensional structure is a space that is not completely closed in a single curled lamellae after the lamellae are folded and curled into a three-dimensional shape, and that cannot enter each other when multiple curled lamellae are stacked.
2. The conductive carbon with a curled sheet structure according to claim 1, characterized in that: The curled monomer length L in the conductive carbon with the curled sheet structure is 20-2000 nm, the curled monomer width W is 20-2000 nm, the curled monomer height H is 20-2000 nm, and the sheet thickness δ is 10-20 nm.
3. The conductive carbon with a curled sheet structure according to claim 2, characterized in that: The DBP oil absorption value of the conductive carbon with the curled lamellar structure is 300-800 ml / 100 g, and the BET specific surface area of the conductive carbon with the curled lamellar structure is 200-800 m² / g.
4. The conductive carbon with a curled sheet structure according to claim 2, characterized in that: The iodine absorption value of the conductive carbon with the curled sheet structure is 200-1200 mg / g, and the electrical conductivity of the conductive carbon with the curled sheet structure is 1-2000 S / m.
5. Application of conductive carbon with curled sheet structure, characterized by: The conductive carbon with curled lamellar structure is mixed with other carbon materials or non-carbon materials to obtain a conductive carbon material rich in curled lamellar structure, and the conductive carbon material rich in curled lamellar structure is used as a negative electrode material for a secondary battery or a positive electrode wrapping material for a secondary battery or a conductive agent or a pigment carbon material.
6. The use of the conductive carbon with a curled sheet structure according to claim 5, characterized in that: The conductive carbon material rich in curled lamellar structure comprises conductive carbon of curled lamellar structure, carbon of other structures and non-carbon impurities, wherein the conductive carbon content of the curled lamellar structure is ≥95%, the carbon content of other structures is ≤4%, and the non-carbon impurity content is ≤1%.
7. The use of the conductive carbon with a curled sheet structure according to claim 5, characterized in that: The carbon with other structures includes amorphous carbon, carbon black and other forms of carbon.
8. The use of the conductive carbon with a curled sheet structure according to claim 5, characterized in that: The non-carbon impurities include ash and volatile matter.
